Optimization of Ultrasound-assisted Extraction of Roselle Flavonoids by Deep Eutectic Solvent and Its Antioxidant Activity - Luyao XU; Yang ZHAO; Yan WANG; Ruoxi GUO; Peng WANG; Lei ZHANG; Han ZHANG; Yuxin ZHAI; Ya'nan LIU (Shipin gongye ke-ji)
This study aimed to optimize the extraction process for roselle flavonoids using an ultrasound-assisted deep eutectic solvent (DES) method and to evaluate flavonoid composition structure and antioxidant capacity. A single factor experiment screening various types of DES was used to investigate the effects of the solid‒liquid ratio, extraction solvent water content, and ultrasonic time, power, and temperature on the flavonoid extraction yield. The extraction parameters were optimized using a response surface methodology, and the structure of flavonoid components was identified. The mechanism underlying DES-mediated extraction was analyzed through infrared characterization and electrostatic potential measurements. Furthermore, in vitro antioxidant assays were employed to assess the antioxidant activity of flavonoids derived from roselle. The optimal extraction process necessitated the following parameters: A choline chloride to lactic acid molar ratio of 1:2, a water content of 14%, a solid-liquid ratio of 1:41 g/mL, an ultrasonic power set at 360 W, an ultrasonic temperature of 40 °C, and an ultrasonic duration of 30 minutes, resulting in an extraction rate of 38.16 mg/g for roselle flavonoids. Infrared and electrostatic potential analysis revealed that DES facilitated efficient extraction primarily through hydrogen bonding. The IC50 values of roselle flavonoids for scavenging DPPH, ABTS+, and OH− free radicals were 6.86±0.21 μg/mL, 4.09±0.25 μg/mL, and 13.42±0.77 μg/mL, respectively. The total reducing power was 2.34 at a concentration of 1 mg/mL. UPLC-Q-TOF-MS preliminarily identified 16 flavonoids in the extract. This study provides a green and efficient method for extracting flavonoids from roselle, providing technical and theoretical support for the further development and utilization of roselle.